Folate Receptor Alpha, Mesothelin and Megakaryocyte Potentiating Factor as Potential Serum Markers of Chronic Kidney Disease. Issue 9 (January 2014) - Somers, Elizabeth B.; O'Shannessy, Daniel J.
Renal disease is the eighth leading cause of death in the United States. Early diagnosis is usually based on the detection of proteinuria or elevated serum creatinine, a relatively poor biomarker that does not accurately predict renal disease progression. As a result, more predictive biomarkers of renal function are sought. We present preliminary data on three protein biomarkers, folate receptor alpha (FRA), mesothelin (MSLN), and megakaryocyte potentiating factor (MPF), currently being pursued for applications in oncology diagnostics, and evaluate serum and urine levels in subjects with renal disease. Compared to healthy subjects, a significant ( P < 0.0001) increase in all three biomarkers in both serum and urine of subjects with renal disease was demonstrated. Further, serum levels of these three protein biomarkers increased with increasing stage of disease suggesting their potential value in predicting progression in subjects with renal disease and raising caution in interpretation of data in oncology applications.